Síntese, análise estrutural e caracterização de novos compostos de coordenação de fenilseleninato de cobre(II) - Leal, Rodrigo Rozado (2010)
In this work were synthesized and studied four new coordination compounds of copper(II) with phenylseleninato ligand, three of them polymeric and one molecular. The reaction of phenylseleninic acid with copper(II) acetate led to microcrystalline light blue powder of polymeric compound catena-poli-[Cu(μ2-O2SePh)2], 1. That powder was used to obtain crystalls of 1 and three others: catena-poli-[Cu(μ2-O2SePh)2(NH3)], 2, obtained by the dissolution of 1 in dmf and aqueous ammonia, catena-poli-[Cu(μ2-O2SePh)2(NC5H5)]·NC5H5, 3, obtained by the dissolution of 1 in pyridine and aqueous ammonia, and poli-[Cu(O2SePh)2(NH3)2(H2O)2], 4, obtained by the dissolution of 1 in water and aqueous ammonia. Compound 1 is a two-dimensional coordination polymer with layers formed by the phenylseleninato double bridges between copper(II) units. The copper(II) centers in the same layer form a (4,4) net topology. Magnetic susceptibility measurements of the crystalline sample of 1 was carried out on a SQUID magnometer and strong ferromagnetic coupling was verified between 10 and 6.3 K. Below 6.3 K was verified a weak antiferromagnetic interactions between partially ordered ferromagnetic layers. All the new compounds were characterized by X-ray diffraction, infrared spectroscopy and elemental analysis. Compounds 2 and 3 have supramolecular nature due to hydrogen bonds in those structures. Only compound 3 is a one-dimensional coordination polymer.